Chronic pain among older adults and its impact on satisfaction with social participation: development and validation of the “Instrument to Assess Older Adults’ Social Participation”: a descriptive quantitative study - Mastela, Gabriela Costa; Galiano, Júlia de Carvalho; Garcia, Ligia Cangussu Tomaz; Arbex, Maria Carolyna Fonseca Batista; Lemos, Naira de Fatima Dutra; Santos, Fania Cristina (São Paulo Medical Journal, 2025)
BACKGROUND: We aimed to develop and validate a practical instrument to assess older adults’ satisfaction with their social participation (SP). DESIGN AND SETTING: This methodological validation study was conducted at a public higher education institution. METHODS: A two-phase study was designed, developed, and validated to assess older adults’ satisfaction with their SP. In the first phase, we conceptualized SP and developed an “instrument to assess older adults’ satisfaction with their SP (IAPSI),” as approved by a committee of specialists, pre-tested, and partially validated. Second, we determined the IAPSI’s reproducibility using Cronbach’s alpha to measure internal consistency, Pearson’s and Spearman’s coefficients to measure correlations, the Bland-Altman plot and intraclass correlation coefficient (ICC) to measure reproducibility. We also generated a receiver operating characteristic (ROC) curve. RESULTS: 102 older adults (mean age, 87.29) participated in the first phase. Moderate internal consistency (Cronbach’s alpha 0.7) and significant moderate correlations with quality of life by World Health Organization Quality of Life (WHOQOL)-bref and by WHOQOL-old social domains (Pearson’s coefficients 0.54 and 0.64, respectively; P < 0.001) were found. The ROC curve indicated an IAPSI score of 17 as the threshold for the impact of pain on satisfaction with SP (83.3% sensitivity and 88.9% specificity, P < 0.001). In the second phase, 56 older adults (between 81 and 90 years old) participated. We found adequate intra- and inter-observer reproducibility for the IAPSI (ICC 0.96 and 0.78, respectively). CONCLUSION: We have developed a practical instrument with appropriate psychometric properties to assess older adults’ satisfaction with their SP.